Allogeneic hematopoietic stem cell transplant recipients and parasitic diseases: A review of the literature of clinical cases and perspectives to screen and follow‐up active and latent chronic infections. Issue 2 (31st March 2017) - Fabiani, Silvia; Fortunato, Simona; Petrini, Mario; Bruschi, Fabrizio
Abstract: Background: Allogeneic hematopoietic stem cell transplant (HSCT) recipients are at substantial risk for a variety of infections depending upon numerous factors, such as degree of immunosuppression, host factors, and period after transplantation. Bacterial, fungal, viral, as well as parasitic infections can occur with high morbidity and mortality. Objectives: The aim of this study was to evaluate the magnitude of the occurrence of parasitic infections in allogeneic HSCT recipients. Modalities of transmission, methods of diagnosis, treatment, donor and recipient pre‐transplant screening and prevention measures of the most serious parasitic infections have also been discussed. Materials and methods: We systematically reviewed literature records on post‐transplant (allogeneic HSCT) parasitic infections, identified through PubMed database searching, using no language or time restrictions. Search was concluded on December 31, 2015. In the present review, we only discussed post‐transplant parasitic infections in allogeneic HSCT. Only exclusion criteria were absence of sufficient information on the transmission of parasitic infection to the recipient. Autologous HSCT recipients have not been included because of the absence of a proper allogeneic transplantation even in presence of blood or blood product transfusions. The methods and findings of the present review have been reported based on the preferred reporting items for systematic reviews and meta‐analysis checklist (PRISMA). Results: Regarding allogeneic HSCT recipients, from data published in the literature the real burden of parasitic infections cannot be really estimated. Nevertheless, a positive trend on publication number exists, probably because of more than one reason: (i) the increasing number of patients transplanted and then treated with immunosuppressive agents, (ii) the "population shift" resulting from immigration and travels to endemic areas, and (iii) the increasing of attention for diagnosis/notification/publication of cases. Conclusions: Considering parasitic infections as emerging and potentially serious in their evolution, additional strategies for the prevention, careful screening and follow‐up, with a high level of suspicion, identification, and preemptive therapy are necessary in transplant recipients. Perspectives: The Authors' viewpoint in the perspective to screen and follow‐up active and latent chronic parasitosis in stem cells donors and recipients: a proposal for a flow chart.